2005
DOI: 10.1002/art.20885
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cartilage damage by overexpression of T cell interleukin‐17A in experimental arthritis in mice deficient in interleukin‐1

Abstract: Objective. To examine the capacity of T cell interleukin-17A (IL-17A; referred to hereinafter as IL-17) to induce cartilage damage during experimental arthritis in the absence of IL-1.Methods. Local IL-17 gene transfer was performed in the knee joint of IL-1-deficient mice and wild-type controls during streptococcal cell wall (SCW)-induced arthritis. Knee joints were isolated at various time points for histologic analysis of cartilage proteoglycan (PG) depletion. Expression of messenger RNA for inducible nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 42 publications
1
72
0
2
Order By: Relevance
“…IL-17 is highly pathogenic to cartilage and bone in various T cell-mediated experimental models of arthritis, including SCW arthritis, and has been shown to be able to take over the catabolic functions of IL-1 (32,34). Importantly, recent evidence indicates that conditioned medium from TLR-4-activated dendritic cells is sufficient to induce Th17 differentiation when TGF␤ is added (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17 is highly pathogenic to cartilage and bone in various T cell-mediated experimental models of arthritis, including SCW arthritis, and has been shown to be able to take over the catabolic functions of IL-1 (32,34). Importantly, recent evidence indicates that conditioned medium from TLR-4-activated dendritic cells is sufficient to induce Th17 differentiation when TGF␤ is added (47).…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible proteoglycan damage by MMP activity in cartilage was assessed by immunostaining for the neoepitope VDIPEN, as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…Enhances IL-1 mediated IL-6 in RA synoviocytes as well as TNF-induced synthesis of IL-1, IL-6, IL-8 [15,16] IL-17 additative/synergistic effect with TNF or IL-1 [33] IL-17 synergize with IL-1, TNF [10,20,32] IL-17 effect is TNF dependent under naïve conditions, but TNF independent under arthritis conditions [38] IL-17 effect is IL-1 independent in experimental arthritis [8,37] IL-17 in bone damage IL-17 induces RANKL in cultures of osteoblasts [13] IL-17 induces bone damage in naïve mice, aggravates bone erosion in CIA [44] Synergy between IL-17 and TNF [20,25,32] IL-17-induced bone erosion is RANKL mediated [44] IL-17 in cartilage damage IL-17 induces NO [34], metalloproteinases in synoviocytes and chondrocytes [17][18][19] Inducer of NO and MMPs and inhibition of PG synthesis [26], aggravates cartilage erosion in CIA [8,9] Synergy between IL-17 and TNF [29] IL-1 independent role of IL-17 in cartilage damage [8,19,28] Th17 IL-17-producing cells in the synovium of RA patients (Th0/Th1 but not Th2) [14] IL-17-producing cells and Th17 in CIA and AIA arthritis models [55,60,70] effects of IL-17 on matrix degradation and synthesis were not dependent on IL-1 production by chondrocytes and IL-1Ra did not block IL-17-induced matrix release nor prevented inhibition of matrix synthesis in vitro using porcine articular cartilage explants [28]. On the other hand, the IL-17 induced production of prostaglandin E2 (PGE2) and nitric oxide (NO) by cartilage explants is LIF-dependent [28,36].…”
Section: Human Studiesmentioning
confidence: 99%
“…On the other hand, the IL-17 induced production of prostaglandin E2 (PGE2) and nitric oxide (NO) by cartilage explants is LIF-dependent [28,36]. Interestingly, an IL-1-independent role of IL-17 in the pathogenesis of experimental arthritis was demonstrated and IL-17 has the capacity to replace the catabolic function of IL-1 in cartilage damage during experimental arthritis [8,37]. Moreover, IL-17 acts independently of TNF under arthritis conditions with no direct role for IL-1 [38].…”
Section: Human Studiesmentioning
confidence: 99%
“…In addition, it was demonstrated that adoptive transfer of IL-23-polarized autoantigen-specific Th17 effector cells were able to transfer EAE more effectively than Th1 cells [9]. IL-17 and IL-23 have also been shown to have a role in the pathogenesis of CIA [10] and colitis [11,12]. These studies established a pathogenic role for Th17 cells in organ-specific autoimmune and chronic inflammatory diseases.…”
mentioning
confidence: 94%